Emerging role of TRP channels in cell migration: from tumor vascularization to metastasis - Fioro Pla, Alessandra; Gkika, Dimitra (Frontiers in Physiology, 2013)
Transient Receptor Potential (TRP) channels modulate intracellular Ca2+ concentrations, controlling critical cytosolic and nuclear events that are involved in the initiation and progression of cancer. It is not, therefore, surprising that the expression of some TRP channels is altered during tumor growth and metastasis. Cell migration of both epithelial and endothelial cells is an essential step of the so-called metastatic cascade that leads to the spread of the disease within the body. It is in fact required for both tumor vascularization as well as for tumor cell invasion into adjacent tissues and intravasation into blood/lymphatic vessels. Studies from the last 15 years have unequivocally shown that the ion channles and the transport proteins also play important roles in cell migration. On the other hand, recent literature underlies a critical role for TRP channels in the migration process both in cancer cells as well as in tumor vascularization. This will be the main focus of our review. We will provide an overview of recent advances in this field describing TRP channels contribution to the process vascular and cancer cell migration, and we will systematically discuss relevant molecular mechanism involved.